Strategic Growth of Everything-as-a-Service (XaaS) Business Model Transformation - Chimakurthi, Venkata Naga Satya Surendra (Engineering International, 2021)
The study presents the XaaS architecture and explores how this business model has strategically developed and how it has revolutionized the whole business industry. The study indicates how this particular business model allows companies to enhance the range of advantages of Internet Cloud model applications, particularly when it deals with process of media processing and customization of users. Its huge benefits with negligible disadvantages are mentioned as part of the presented research. This study will help to understand the services of XaaS model, challenges experiencing by it and its future opportunities. This will also assists new scholars of field to build a better understanding and better prospects regarding XaaS in future.
Keywords: XaaS; Internet cloud; Business model